Place the Sheath: Emergent 7 French Femoral Sheath Placement is Low Risk During Initial Trauma Resuscitation - Cralley, Alexis L; DeBot, Margot; DeBot, Margot; Hadley, Jamie; Pieracci, Fredric; Platnick, Barry K; Campion, Eric; Moore, Ernest E; Cohen, Mitchell J; Fox, Charles J; et al. (Journal of Endovascular Resuscitation and Trauma Management, 2023)
Background: We hypothesized that emergent placement of 7 French (Fr) common femoral artery (CFA) sheaths during trauma resuscitation for potential resuscitative endovascular balloon occlusion of the aorta (REBOA) carries a low complication rate. Methods: Trauma patients at a Level I trauma center with emergent CFA access from January 2016 through to December 2020 were reviewed. CFA access was categorized as (1) 7 Fr sheath plus REBOA (REBOA) and (2) 7 Fr sheathwithout REBOA (Sheath). Outcomes included mortality and vascular complications. Results: 157 patients underwent emergent CFA access. Sixty-nine (43.9%) patients had a 7 Fr CFA sheath, and 88 (56.1%) progressed to REBOA. The mortality rate was similar (Sheath 30.4% vs. REBOA 34.1%, p = 0.63). The REBOA cohort had a significantly higher complication rate (22.7%) compared to the Sheath cohort (4.3%, p = 0.001). Conclusions: Emergent 7 Fr CFA sheath placement during trauma resuscitation is low risk, suggesting empiric sheath placement is warranted in potential REBOA candidates.